2020
DOI: 10.3390/nu12061739
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Rosmarinus officinalis L.: Mechanisms of Action and Therapeutic Potentials

Abstract: Alternative treatments for neoplastic diseases with new drugs are necessary because the clinical effectiveness of chemotherapy is often reduced by collateral effects. Several natural substances of plant origin have been demonstrated to be successful in the prevention and treatment of numerous tumors. Rosmarinus officinalis L. is a herb that is cultivated in diverse areas of the world. There is increasing attention being directed towards the pharmaceutical capacities of rosemary, utilized for its anti-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 141 publications
0
50
0
1
Order By: Relevance
“…The anticancer activity of rosemary has been investigated in several types of cancer [ 16 ]. Carnosic acid, a major derivative of rosemary, has been linked with various biological activities, including antioxidant effects, epigenetic modification, anti-inflammatory activity, and regulation of immune systems [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer activity of rosemary has been investigated in several types of cancer [ 16 ]. Carnosic acid, a major derivative of rosemary, has been linked with various biological activities, including antioxidant effects, epigenetic modification, anti-inflammatory activity, and regulation of immune systems [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer activities of rosemary extracts have been intensively studied, as summarized in a recent review [ 25 ]. For example, several reports have shown that CA induces apoptosis in HepG2 cells [ 26 , 27 ], but its anticancer activity through AMPK activation has yet to be fully clarified, though CL does inhibit the growth of human prostate cancer PC3 cells at least partly via AMPK activation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carnosol exerts long term antioxidant effect by activating phosphatidylinositol 3-kinase (PI3K)/Akt pathway and HO-1 pathways [29]. Furthermore, many signaling molecules are implicated in the anticancer properties of carnosol including molecules associated with cell cycles including PI3K/Akt, mammalian target of rapamycin (mTOR), and 5'-AMP-activated protein kinase (AMPK) and androgen and estrogen receptors [25,30,31] .…”
Section: Discussionmentioning
confidence: 99%